Implement of multiple access technique by wireless power transfer and relaying network - Anh-Tu Le; Dinh-Thuan Do (Bulletin of Electrical Engineering and Informatics, 2021)
In this paper, we investigate non-orthogonal multiple access (NOMA) network relying on wireless power transfer to prolong lifetime. The base station (BS) sends common signals to the relay with two functions (energy harvesting (EH) and signal processing) to further serve two NOMA users in downlink. Performance gap exists since different power allocation factor assigned from power splitting protocol adopted at the relay and such relay employs both amplify-and-forward (AF) and decode-and-forward schemes. To provide performance metrics, we prove formulas of the outage probability which is a function of transmit signal to noise ratio. Simulation results indicate specific parameters to adjust system performance of two user in the considered EH-NOMA system. This finding is important recommendation to design EH-NOMA which shows particular outage performance at required target rates.